2017
DOI: 10.1016/j.fm.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of methicillin-resistant Staphylococcus aureus (MRSA) isolated from milk and dairy products in South Italy

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen emerging in hospitals as well as community and livestock. MRSA is a significant and costly public health concern because it may enter the human food chain and contaminate milk and dairy products causing foodborne illness. This study aimed to determine the occurrence and the characteristics of MRSA isolated from 3760 samples of milk and dairy products in a previous survey conducted in southern Italy during 2008-2014. Overall out of 484 S. aureus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
104
8
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 54 publications
17
104
8
5
Order By: Relevance
“…This result is similar to those published by Traversa et al (2015) and Papadopoulos et al (2018). A contrary result was reported by Basanisi et al (2017) who indicated a prevalence of 50% for the pvl gene among MRSA isolates from milk and dairy. In addition, a survey performed in Turkey demonstrated the presence of one pvl-positive MRSA strain originating from cheese (Sudagidan & Aydin, 2010).…”
Section: S Aureussupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to those published by Traversa et al (2015) and Papadopoulos et al (2018). A contrary result was reported by Basanisi et al (2017) who indicated a prevalence of 50% for the pvl gene among MRSA isolates from milk and dairy. In addition, a survey performed in Turkey demonstrated the presence of one pvl-positive MRSA strain originating from cheese (Sudagidan & Aydin, 2010).…”
Section: S Aureussupporting
confidence: 90%
“…The presence of MRSA in milk was reported by Li, Zhou, Wang, Xue, and Zhao () who found one mecA ‐positive and seven mecA ‐negative but phenotype‐positive MRSA strains in milk samples (Li et al, ). Studies performed during the last decade in different countries indicated the presence of mec A‐positive and/or phenotype‐positive MRSA (Basanisi, La Bella, Nobili, Franconieri, & La Salandra, ; Carfora et al, ; Kamal, Bayoumi, & Abd El Aal, ; Song et al, ; Traversa et al, ) in milk. The occurrence of MRSA in milk was also reported by researches from Turkey (Buyukcangaz et al, ; Pamuk, Yildirim, Seker, Gurler, & Kara, ; Siriken, Yildirim, Güney, Erol, & Durupinar, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same tendency, the binding and/or insertion ability of S. aureus to mammary gland epithelium was related to the production of biofilms [13]. In addition, biofilm formation limits antimicrobial agents therapy of mastitis by reducing the diffusion of antibiotics through the biofilm matrix [14,63].…”
Section: Discussionmentioning
confidence: 98%
“…MRSA carriage or infections were described mostly in farm animals, such as pigs [19], cattle [20], sheep [21], horses [22] or poultry [23]. Transmission to humans has been documented, mostly after prolonged, repeated and close contact with a colonized animal [24] or through a contaminated vehicle such as meat [25] or dairy products [26]. Several studies confirmed the presence of MRSA ST398 in pigs, goats, cow and sheep and their meat and milk products in the Czech Republic [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%